Does the Long-Term Interest Rate Predict Future Inflation? A Multi-Country Analysis - Engsted, Tom (The Review of Economics and Statistics, 1995)
According to the Fisher hypothesis, an increase (decrease) in the spread between the long-term, or multiperiod, interest rate and the one-period inflation rate signals an increase (decrease) in future one-period inflation. This implication is tested on data from thirteen OECD countries for the period 1962-93. Integration and cointegration techniques are applied to examine the time-series properties of interest rates and inflation rates, and the VAR methodology developed by John Y. Campbell and Robert J. Shiller (1987) is applied to examine the predictive power of the spread as well as in testing the Fisher hypothesis under rational expectations and constant ex ante real rates. Copyright 1995 by MIT Press.